Une marrane devant le Saint-Office de l’Inquisition, México, 1642-1649. Isabel Tristán, « La Tristana » - Solange Alberro (Caravelle)
Isabel Tristán, born in Spain, was a rich widow very much appreciated in the Mexican society towards the middle of the 17th century. All of her family of Jewish origin suffered the rigours of the Saint Office, first from the peninsular one and then from the one in New Spain. She was herself a very zealous as well as a very secret practising of Mosaic. Denounced to the Saint Office by several testimonies, torture didn’t break her, and Tristana didn’t confess anything new to the inquisitors. Because of her strong and haughty character she was sentenced to be burnt at the stake.